An Anti‐Freezing, Ambient‐Stable and Highly Stretchable Ionic Skin with Strong Surface Adhesion for Wearable Sensing and Soft Robotics. (28th July 2021) - Ying, Binbin; Chen, Ryan Zeyuan; Zuo, Runze; Li, Jianyu; Liu, Xinyu
Abstract: Natural living systems such as wood frogs develop tissues composed of active hydrogels with cryoprotectants to survive in cold environments. Recently, hydrogels have been intensively studied to develop stretchable electronics for wearables and soft robots. However, regular hydrogels are inevitably frozen at the subzero temperature and easily dehydrated, and have weak surface adhesion. Herein, a novel hydrogel‐based ionic skin (iSkin) capable of strain sensing is demonstrated with high toughness, high stretchability, excellent ambient stability, superior anti‐freezing capability, and strong surface adhesion. The iSkin consists of a piece of ionically and covalently cross‐linked tough hydrogel with a thin bioadhesive layer. With the addition of biocompatible cryoprotectant and electrolyte, the iSkin shows good conductivity in wide ranges of relative humidity (15–90%) and temperature (−95–25 °C). In addition, the iSkin can adhere firmly to diverse material surfaces under different conditions, including cloth fabric, skin, and elastomers, in both dry and wet conditions, at subzero temperature, and/or with dynamic movement. The iSkin is demonstrated for applications including strain sensing on both human body and winter coat, human–machine interaction, motion/deformation sensing on a soft gripper and a soft robot at extremely cold conditions. This work provides a new paradigm for developing high‐performance artificial skins for wearable sensing and soft robotics. Abstract : A novel hydrogel‐based ionic skin (iSkin) is rationally designed to achieve high toughness, high stretchability, good conductivity, excellent ambient stability, superior anti‐freezing capability (−95 °C), and strong adhesion to various surfaces. The iSkin is demonstrated for strain sensing under extreme conditions, with applications to wearable sensing, sports monitoring, human–machine interaction, and soft robotic sensing.